PERANAN GAYA KOMUNIKASI GURU DALAM MENDUKUNG PERKEMBANGAN MORAL SISWA DI SMPN 1 KIKIM TIMUR - Suranto, M Ridho; Saputra, Sepriadi; Ritonga, Muslimin (AN-NASHIHA Journal of Broadcasting and Islamic Communication Studies, 2025)
The communication style of their teachers has a significant influence on students' moral and character development in the classroom. The purpose of this study was to investigate how SMPN 1 Kikim Timur teachers foster and mold their students' morals through interpersonal communication. The study employs a qualitative methodology that includes in-depth interviews with key teacher informants, as well as observational data. The study examines the phases, tactics, and relationships between teacher-student interactions and moral growth under the framework of the Social Penetration Theory. According to research, educators employ flexible communication techniques, assuming the roles of mentor, father, and friend as needed. This strategy effectively promotes openness, trust, and the absorption of moral principles in students' daily lives. The application of the Triangle of Restitution technique supports the effectiveness of structured communication tactics in guiding students through discipline difficulties and establishing responsibility. Students' defensive barriers and closed attitudes are the biggest challenges, but they can be overcome with relational and regular communication. In conclusion, students' positive moral growth is greatly influenced by the adaptability and depth of teachers' communication.